2022
DOI: 10.14254/2071-789x.2022/15-1/17
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social media use on the internationalisation of SMEs

Abstract: Social media (SM) are one of the marketing tools growing in importance with increasing digitalisation. Companies use marketing to increase interest in their services or reach new customers. Therefore, SM can help companies access a new international market. The aim of this paper is to determine the impact of SM as a marketing strategy tool to gain a new market in the process of internationalisation of SMEs in the countries of Visegrad Four. The paper also evaluates differences in SM approaches according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…The development of entrepreneurship in the online environment has led to increased attention of scientists in this area. Thus, both domestic and foreign scientists such as Z. Wilger, J. Kramolish, N. Kapolupo [1], E. Ikechukwu, A. Emmanuel, I. Edjikeme [2], pay attention to the functioning of enterprises on the Internet. Sadigov [3], A. Hamvon [4], D. Tavorn, P. Trichob, V. Klongtong, C. Ngamkroekjoti [5], I. Otenko [6], S. Ilyashenko [7], O. Belovodskaya [8], T. Ilchenko [9], D. Doroshkevich [10] and others.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of entrepreneurship in the online environment has led to increased attention of scientists in this area. Thus, both domestic and foreign scientists such as Z. Wilger, J. Kramolish, N. Kapolupo [1], E. Ikechukwu, A. Emmanuel, I. Edjikeme [2], pay attention to the functioning of enterprises on the Internet. Sadigov [3], A. Hamvon [4], D. Tavorn, P. Trichob, V. Klongtong, C. Ngamkroekjoti [5], I. Otenko [6], S. Ilyashenko [7], O. Belovodskaya [8], T. Ilchenko [9], D. Doroshkevich [10] and others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sadigov [3], A. Hamvon [4], D. Tavorn, P. Trichob, V. Klongtong, C. Ngamkroekjoti [5], I. Otenko [6], S. Ilyashenko [7], O. Belovodskaya [8], T. Ilchenko [9], D. Doroshkevich [10] and others. It should be noted that, for example, Z. Wilger, J. Kramolish and N. Kapolupo in their work "The impact of social media on the internationalization of SMM" [1] identify the impact of social media as a tool of marketing strategy in the economy of impressions to conquer new markets. The authors present the results of an empirical study for 2019-2020 to assess the differences in approaches to social networks according to some factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Smaller enterprises can perceive the higher related costs and the need to employ experts as a specific constraint in using more complex methods. This peculiarity is typical for current business activity, even considering the increasing demand for IT products implementation in business management (Balcerak & Woźniak, 2021;Luchko, Arzamasova & Vovk, 2019;Roshchyk et al, 2022;Szeiner et al, 2022), including artificial intelligence-based ones (Bencsik, 2021;Šuleř & Machová, 2020) and other digital tools of modeling and data collection within management systems in enterprises (Adda et la., 2021;Akimova et al, 2020;Bilan et al, 2017;Mura & Hajduová, 2021;Virglerová et al, 2022;Jeza & Lekhanya, 2022). Therefore, we also perform a multicriteria evaluation of the models in this study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Marketing through social media such as Instagram or Facebook can create a new direction for MSMEs to connect with their customers (Abbasi et al, 2022). Viglerová et al (2022) stated several pillars as the main characteristics of marketing through social media, such as internet applications, electronic word-of-mouth (E-WoM), and interaction. It was evidenced by Fahmi et al (2022) and Asnawati et al (2022) who suggested that social media marketing can increase brand image globally and E-WoM significantly influences company marketing.…”
Section: Introductionmentioning
confidence: 99%